Escovopsis kreiselii specialization to its native hosts in the fungiculture of the lower attine ant Mycetophylax morschi - Custodio, Bruna Cristina [UNESP]; Rodrigues, Andre [UNESP] (Springer Nature, 2018)
Parasite-host associations are widespread in nature and the fungus-growing ants are considered model organisms to study such interactions. These insects cultivate basidiomycetous fungi for food, which are threatened by mycotrophic fungi in the genus Escovopsis. Although recently described from colonies of the lower attine ant Mycetophylax morschi, the biology and pathogenicity of Escovopsis kreiselii are unknown. Herein, we evaluated the interaction of E. kreiselii with fungi cultivated by M. morschi (native hosts) and with a fungus cultivated by another attine ant species (non-native host). In addition, we examined the physical interactions between hypha of E. kreiselii and hypha from its native hosts using scanning electron microscopy. Escovopsis kreiselii inhibited the growth of fungal cultivars by 24% or more (with exception of one isolate), when compared to the fungal cultivars growing alone. Escovopsis kreiselii is attracted towards its native hosts through chemotaxis and inhibition occurs when there is physical contact with the hyphae of the fungal cultivar. As reported for Escovopsis parasites associated with leafcutter ants (higher attines), E. kreiselii growth increased in the presence of its native hosts, even before contact between both fungi occurred. In interactions with the fungal cultivar that is not naturally infected by E. kreiselii (non-native host), it caused inhibition but not at the same magnitude as in native hosts. Multiple lines of evidence suggest that E. kreiselii is an antagonist of the fungus cultivated by M. morschi and can chemically recognize such fungus.
Keywords: Antagonism; Chemotaxis; Fungal interactions; Host-parasite